Synthesis of Antibacterial and Biodegradable Bioplastic Based on Shrimp Skin Chitosan and Durian Skin Cellulose with the Microwave Assistance - Mashuni Mashuni; La Ode Ahmad; Emiliana Sandalayuk; Fitri Handayani Hamid; M Jahiding; Andi Muhammad Naufal Khaeri (Jurnal Kimia Valensi, 2022)
This study aimed to obtain the best composition in the synthesis of antibacterial bioplastics made from chitosan from shrimp skin (SS) and cellulose from durian skin (DS). The research method began with the isolation of chitin from SS. Then it was deacetylated using a microwave (MW) at 60 °C for 15 minutes at 400 watts of power in an alkaline solution. The extraction of cellulose from DS through delignification using the MW for 20 minutes, 300 watts of power in Na2SO3 solution. Synthesis of bioplastics is made from variations in the composition of chitosan (8, 12 and 16% w/w), cellulose and glycerol as a plasticizer. The characterization of bioplastics with FTIR obtained functional groups O–H, C–H, C=O, C–N and N–H amines, and SEM characterization obtained bioplastic has fibre and pore size 15.429 µm. The best bioplastic characteristics were the composition of 12 % chitosan, with tensile strengths of 13.28 Mpa, water resistance of 79 % and the ability to degrade 52.67% after 15 days have met international plastic standards (ASTM 5336). The antibacterial activity of bioplastics against Escherichia coli and Staphylococcus aureus with the Disc diffusion method showed the presence of moderate zones category of inhibition so that the resulting bioplastics can be recommended as food packaging that is environmentally friendly and antibacterial.